Long-Term Trends of Planted Loblolly Pine Diameter Distribution Characteristics. Issue 3 (12th April 2021) - Green, P Corey
Abstract: Diameter distributions are fundamental characteristics of stand structure. It is widely assumed that unthinned plantation loblolly pine ( Pinus taeda L.) diameter distributions are unimodal and slightly skewed. In this work, the assumption of unimodality is formally tested and confirmed using 413 long-term permanent plots representing three generations of genetics and silviculture across the native range of loblolly pine in the southeastern United States. Approximately 96% of plot measurements had no significant evidence to reject the hypothesis of unimodality. While levels often significantly differed, similar developmental trends of skewness, kurtosis, and estimated Weibull parameters were observed despite the advances of genetics and silviculture. The results of the study indicate the continued need for a flexible distribution for characterizing diameter distributions in plantation loblolly pine.